Evaluation and prognosis of neonates with asphyxia treated by hypothermia - Abdollah Jannatdoust; Mohammad Barzegar; Mohammad bagher Hosseini; Behanam Asghari; Farzad Ilkhchooyi (Mashhad University of Medical Sciences, 2014)
Background: Asphyxia is a perinatal accident with a high mortality rate, therapeutic hypothermia in both head or whole body was suggested as effective therapeutic methods. In this study, we compare these methods in neonates with asphyxia.Methods and Materials: 16 neonates with asphyxia in two hospitals including Alzahra(head hypothermia) and Taleghani hospital (total body hypothermia) went under the therapeutic hypothermia for 72 hours. Maintaining temperature controlled by several sensors precisely. Body cooling were performed on the trunk and limbs of the neonates. Temperature and vital signs controlled every 1 hour and biochemistry, and coagulation tests were performed regularly, early and late complications of patients including developmental disorders, were evaluated. Comparing two groups was performed using Chi square and Mann Whitney U test, on the software SPSS16 , p less than 0.05 was significant.Results: 16 cases with gestation age of 38 ± 2weeks were enrolled. Of 9 cases by head cooling 1 patient died and 2 patients got mild developmental disorders. Of the 7 newborns of whole body cooling trail, 3 died and 1 got minor developmental disorders and one case showed major.. Feeding time (head group 5±2 , body group 8±5 days) and also discharge time (head group 15±8 days and body group 14±5 days ) had no significant differences .Conclusion: It seems head hypothermia method is associated with a lower mortality than the whole body method. In the above sample size, the differences were not statistically significant. Performing these procedures on larger samples could be approval.